Block Copolymer‐Directed Synthesis of Conjugated Polyimine Nanospheres with Multichambered Mesopores. Issue 11 (8th May 2020) - Jiang, Xiaolin; Ai, Yan; Han, Zhuolei; You, Yuxiu; Luo, Hao; Cui, Jing; Wei, Facai; Fu, Jianwei; He, Qingguo; Cheng, Jiangong; Liu, Shaohua
Abstract: Conjugated polyimines constructed from aromatic amines and aromatic aldehydes have attracted enormous attention because of their excellent and fascinating properties. However, the structure of these materials constructed by building blocks or linkers is usually confined to a scope of microporosity and small mesopores (less than 5 nm), which largely impedes their applications in many fields. Here, a facile self‐assembly strategy is developed to controllably fabricate conjugated polyimines nanospheres with multichambered mesoporous architecture by using polystyrene‐ b ‐poly(acrylic acid) diblock copolymer as a soft template. Given the wide availability of amines and aldehydes, it is expected to open new avenues for designing diverse polyimine‐based materials with controlled mesostructure toward applications. Abstract : A facile self‐assembly strategy is developed to synthesize mesoporous conjugated polyimine nanospheres by using polystyrene‐ b ‐poly(acrylic acid) diblock copolymer as a soft template, which feature the well‐defined multichambered mesopores (≈20 nm) and monodisperse spherical architecture (≈200 nm).